Embryonal rhabdomyosarcoma at an unusual age and in an atypical site: a case report - Ayla Kouli; Mouna Baddoura; Miriam Laflouf; Seham Sulaiman (Journal of Medical Case Reports)
Abstract Background Rhabdomyosarcoma is classified into histologic subtypes: embryonal, alveolar, pleomorphic, spindle, and mixed-type. Embryonal rhabdomyosarcoma is mainly a disease of children. It occurs rarely in adults. When rhabdomyosarcoma is found in adults, it usually exhibits worse outcomes than in pediatric patients. Case presentation We present a case report of a 20-year-old Arab woman who presented with generalized musculoskeletal pain, unintended weight loss, and excessive night sweats. There was no remarkable history of medications, diseases, or surgeries. A positron emission tomography scan showed multiple osteolytic lesions with metabolic activity, as well as pleural effusion and soft tissue mass around the thoracic area. Following this, a bone marrow biopsy was performed and showed metastatic embryonal rhabdomyosarcoma according to immunochemistry stainings. Chemotherapy was started with 3 doses of vincristine, actinomycin D, and cyclophosphamide regimen for 3 months, after which a positron emission tomography scan showed a total disappearance of the soft tissue mass, but revealed metabolic activity of new foci. Therefore, the patient took another 3 doses of the vincristine, actinomycin D, and cyclophosphamide regimen, and received a total of 30 Gy of radiotherapy on the new foci. Conclusion This paper describes a case of a patient diagnosed with adult rhabdosmyosarcoma at an uncommon age and in an uncommon site; therefore, it is important to consider rhabdomyosarcoma in the differential diagnosis of patients given an abnormal presentation and unexplained findings. Early detection of the disease, which is difficult with nonspecific symptoms, is crucial for improving outcomes.